2020
DOI: 10.1177/0300060520928788
|View full text |Cite
|
Sign up to set email alerts
|

Modified transperitoneal versus retroperitoneal laparoscopic radical nephroureterectomy in the management of upper urinary tract urothelial carcinoma: Best practice in a single center with updated results

Abstract: Objective Radical nephroureterectomy remains the gold standard for the surgical treatment of upper urinary tract urothelial carcinoma (UTUC). Based on previous research, we prospectively compared the advantages of transperitoneal laparoscopic radical nephroureterectomy (TLNU) with a three-port technique in a single position versus retroperitoneal laparoscopic radical nephroureterectomy (RLNU). Methods We evaluated 48 patients diagnosed with UTUC at our institution from January 2015 to October 2019. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…RLRN has smaller surgical incision, less postoperative pain, and less impact on gastrointestinal function of patients, which can help patients recover gastrointestinal function at an early stage, shorten postoperative feeding time of patients, and enable patients to get out of bed and exercise as soon as possible. Moreover, RLRN has less trauma, clear surgical approach, no need for incision of the peritoneum, and less separated abdominal tissues, which can avoid long-term exposure of abdominal organs, effectively improve the injury and pollution of other abdominal organs, and contribute to postoperative recovery [ 26 , 27 ]. The results of this study showed that the total incidence of postoperative complications in the observation group was lower than that in the control group, and the levels of serum IL-6 and TNF- α were lower than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…RLRN has smaller surgical incision, less postoperative pain, and less impact on gastrointestinal function of patients, which can help patients recover gastrointestinal function at an early stage, shorten postoperative feeding time of patients, and enable patients to get out of bed and exercise as soon as possible. Moreover, RLRN has less trauma, clear surgical approach, no need for incision of the peritoneum, and less separated abdominal tissues, which can avoid long-term exposure of abdominal organs, effectively improve the injury and pollution of other abdominal organs, and contribute to postoperative recovery [ 26 , 27 ]. The results of this study showed that the total incidence of postoperative complications in the observation group was lower than that in the control group, and the levels of serum IL-6 and TNF- α were lower than those in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, we determined six studies published between 2016 and 2022 that passed our initial title and abstract screening. One study was a prospective non-randomized controlled trial [ 11 ], while the other five studies were retrospective observational case–control studies [ 12 – 16 ]. One of the trials is a multi-center study [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [ 11 – 16 ] reported postoperative complications, such as postoperative bleeding, fever, intestinal obstruction, etc. No statistically significant difference was observed between the two surgical approaches in the incidence of Clavien-Dindo grade I ( P = 0.78) and grade II ( P = 0.62) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this approach, the lower segment of the ureter including the intramural ureter is managed in the same position. Although this operation is performed under direct vision, difficulties such as operator discomfort and unsatisfactory surgical field of view remain [3, 15, 16]. In addition, the patients still need a lithotomy position to have cystoscopy to treat the potential bladder tumor pre-operation.…”
Section: Discussionmentioning
confidence: 99%